Politics and Gender in Crisis in David Underdown's "The Taming of the Scold". Issue 5 (30th May 2013) - Weil, Rachel; Smuts, Malcolm
Abstract David Underdown's 1985 essay "The Taming of the Scold" argues on the basis of an increase in the number of cucking stools and skimmingtons (both mechanisms for punishing unruly women) that there was a crisis in gender relations in the years around 1600. This article reviews the argument, describes the diverse historiographies with which it engages and contributes, and considers later attempts to test Underdown's claims empirically and the methodological questions which these attempts illuminate.